O Discurso socialista cubano contemporâneo sobre deserção: uma análise dos pronunciamentos de Fidel Castro - Colaça, Joyce Palha (2010)
This research attempts to understand the process of producing meanings about desertion in the contemporary Cuban socialist discourse. To that purpose, they were selected sixteen Fidel Castro s announcements held from June 2007 to March 2009, which regarded desertion affairs in Cuba. The study has been developed upon theoretical assumptions of French Discourse Analysis, formulated by Michel Pêcheux and later developed by Eni Orlandi and other researchers in Brazil and France. The analysis show that, as far as the Cuban socialist discourse is concerned, the work on designations is fundamental to build up the meanings related to desertion and deserters, socialist and capitalist governments, together with Cuba itself. Furthermore, as for this theory, sense and subject are mutually constituted, it has emphasized the analysis of subject-positions filled in the discourses uttered by the Cuban ex- Commander-in-Chief. Finally, it was observed that the mechanism of expectation and argumentation strategies, combined with the work on designations, and the varied subjectpositions in the discourse, play basic roles, functioning towards the maintenance of the socialist government in the islands.